Psychodramatic resource in the intervention for adult sex offender - dos Santos Wolff, Lana (2020)
This text aims to propose the use of an intermediate object and the “as if” technique as reflexive mediators needed in a psychosocial intervention addresses to perpetrators of sex violence against children and adolescents. It is a documentary research carried out in a health institution. Fourteen adult sex offenders participated of this study and joined a psychossocial intervention in group, developed in eight sessions, that are described herein. The introduction of the “as if” decreases the tension during the discussion of the themes and also provides opportunities for greater expression during action. The adoption of the intermediate object creates a recreational context that assists the interaction among the participants. The theoretical and practical orientation of psychodrama allows focused on themes that have great social and moral commitment